2019
DOI: 10.1016/j.jvs.2018.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Episode-based cost reduction for endovascular aneurysm repair

Abstract: Excessive costs associated with EVAR threaten the sustainability of these procedures in health care organizations. Targeted cost reduction efforts can effectively reduce expenses without compromising quality or limiting patients' access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…8 The overall cost effectiveness becomes even more relevant when considering readmission and reinterventions. 5,8,9 Interventions and pathways have been established to help reduce costs. By focusing on implant, rooming, and imaging expenses, significant cost savings were achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The overall cost effectiveness becomes even more relevant when considering readmission and reinterventions. 5,8,9 Interventions and pathways have been established to help reduce costs. By focusing on implant, rooming, and imaging expenses, significant cost savings were achieved.…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on implant, rooming, and imaging expenses, significant cost savings were achieved. 9 Some institutions have implemented same day discharges after EVAR, but a cost analysis was not performed. 4 Other institutions have implemented an EVAR fast-track discharge pathway to reduce cost and one study reported that fast-track EVARs, compared to standard EVAR discharge pathway, had a shorter total length of stay by .6 day that did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(43) Some studies report the reduction of expenses with stent grafts for aortic aneurysms by up to 30.8%, from the restructuring of contracts for the acquisition of materials, comparison of prices in the market, and transparency in negotiations with suppliers. (44) Thinking about strategies at a national level, stimuli such as tax incentives or the development of a structure that would allow national manufacturing may help reduce the costs of endovascular materials, allowing greater diffusion of these techniques.…”
Section: ❚ Costs Of Materialsmentioning
confidence: 99%
“…40 This pilot study provided all centers with more accurate and trusted cost benchmarking, due to the granular clinical data, and allowed Stanford surgeons to significantly reduce the costs of implants, bed utilization, inpatient imaging, and medications. 41 Ultimately, the combination of clinical outcomes with cost data allows calculation of value. One method to define quality is the avoidance of major adverse event rates, which can be adjusted for severity based on the associated, prolonged LOS.…”
Section: Vascular Quality Initiative and Cost Reductionmentioning
confidence: 99%